ANALISIS PENGUATAN SUMBERDAYA DAERAH DALAM PELAKSANAAN SMART GOVERNANCE DI KOTA BALIKPAPAN, KALIMANTAN TIMUR - muhammad nawawi; Muh Ilham; irfan setiawan (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
The aim of this research is to study and analyze how the implementation of smart governance in the city of Balikpapan, how to strengthen local resources in the implementation of smart governance in the city of Balikpapan, and how to strengthen local government resources in supporting Smart Governance in Balikpapan City. The results of the analysis and discussion was found that the implementation of smart governance in the city of Balikpapan in serving the needs of the community could be carried out well if coupled with strengthening local government resources that include institutions, budgets and IT apparatus on the dimensions of local government, and increasing community participation and community use towards applications in the community dimension.